When you hear me (you hear us) : voices on youth incarceration - Senghor, Shaka (Free Minds Book Club & Writing Workshop, 2022)
"When You Hear Me (You Hear Us) is an anthology of poetry and personal stories centering the voices of those directly impacted by the incarceration of young people in the United States. Compiled by Free Minds Book Club & Writing Workshop, this rich collection includes firsthand accounts from both the young people charged and incarcerated in the adult criminal legal system and from the community at large: the mothers, the loved ones, the correctional staff, public defenders, prosecutors, and others harmed and left with unhealed trauma. These critical voices, uniquely combined, illustrate the ecosystem that surrounds youth who are incarcerated--and expose the ripple effects that touch us all. This book challenges us to hear these voices calling out for accountability, transformative justice, and healing. Together, they demonstrate the collective impact of the prison system, and our collective responsibility to create a society where every one of us can thrive."--Amazon website.